Fair game ebook - Briggs, Patricia (Alpha and Omega, 2012)
#1 New York Times bestselling author Patricia Briggs' third Alpha and Omega novel brings werewolves out of the darkness and into a society where fear and prejudice could turn the hunters into the prey… It is said that opposites attract. And in the case of werewolves Anna Latham and Charles Cornick, they mate. The son—and enforcer—of the leader of the North American werewolves, Charles is a dominant Alpha. While Anna, an Omega, has the rare ability to calm others of her kind. When the FBI requests the pack’s help on a local serial-killer case, Charles and Anna are sent to Boston to join the investigation. It soon becomes clear that someone is targeting the preternatural. And now Anna and Charles have put themselves right in the killer’s sights...